The Role of Human Milk Immunomodulators in Protecting Against Viral Bronchiolitis and Development of Chronic Wheezing Illness - Dani-Louise Dixon (MDPI AG, 2015)
Infants who are breastfed are at an immunological advantage when compared with formula fed infants, evidenced by decreased incidence of infections and diminished propensity for long term conditions, including chronic wheeze and/or asthma. Exclusive breastfeeding reduces the duration of hospital admission, risk of respiratory failure and requirement for supplemental oxygen in infants hospitalised with bronchiolitis suggesting a potentially protective mechanism. This review examines the evidence and potential pathways for protection by immunomodulatory factors in human milk against the most common viral cause of bronchiolitis, respiratory syncytial virus (RSV), and subsequent recurrent wheeze in infants. Further investigations into the interplay between respiratory virus infections such as RSV and how they affect, and are affected by, human milk immunomodulators is necessary if we are to gain a true understanding of how breastfeeding protects many infants but not all against infections, and how this relates to long-term protection against conditions such as chronic wheezing illness or asthma.